Potensi Kayu Perkakas dan Kayu Bakar Jenis Jati (Tectona grandis) di Hutan Rakyat Desa Natah, Gunung Kidul - Ris Hadi Purwanto; Dian Asih Kurniasari (Jurnal Ilmu Kehutanan, 2009)
Potentials  of Merchantable Timber and Firewod of Teak (Tectona grandis) in Natah Village Community Forest , GunungkidulThe potential of merchantable timber and firewod of teak (Tectona grandis) in Desa Natah community forest was estimated by developing allometric equations method. To establish the allometric equation 350 sample trees were measured to determine the relationships between tree height (H) and diameter breast height (D). Thirty trees of various sizes were cut to measure the merchantable timber and firewood volume. The raw merchantable timber volume of teak in the community forest was defined as the ligneous material contained in the bole and branches which both with a diameter of at least 10cm. The result showed that D (taken at about 1.3m above the ground) was a good predictor of H with r2 over 0.9672. When D was combined with H, r2 was improved somewhat for the merchantable timber volume, suggesting the growth patterns of tree dimensions were colesy interdependent. A standing stock of the merchantable timber and firewood volume of teak in the community forest was then estimated based on the allometric relations. Proportions of the merchantable timber and firewood volume were 66.91% and 33.09% of total wood volume per tree, respectively. The potential of merchantable timber and firewood volume in these community forest were 13.501 m3/ha and 8.686 m3/ha, respectively, with a basal area of 1.887 m2/ha. Based on the basal area, Desa Natah community forests of teak could be classified into extremely sparse of stands category.